Factors affecting participatory communication for development: the case of a local development organization in Ethiopia - Ali, Adem Chanie; Sonderling, Stefan (Penerbit Universiti Kebangsaan Malaysia, 2017)
The research set out to explore the major factors affecting the practice of participatory communication (PC) in development processes using the development and aid works experiences of a leading local NGO in Amhara National Regional State (ANRS) called Organization for Rehabilitation and Development in Amhara (ORDA) as a case study. This qualitative case study used in-depth interview, Focus Group Discussion (FGD), and document analysis and field observation for data collection. The study was framed based on the participatory model of development which has been assumed to bring about sustainable socio-economic change of a country. The research reveals the presence of several factors affecting the practice of participatory development communication in ORDA. The factors could be divided into three sub themes which include the individual, the institutional and the environmental factors. Because of such pressing factors participatory communication is marginalized and genuine participation is the missing link in the development process. To avert such trends, the paper calls for professionalism for the development communication, structural change of the organization and holistic approach of development for successful development endeavors.